Pollution in the Press: Employing Text Analytics to Understand Regional Water Quality Narratives - Caballero, Mariah D.; Gunda, Thushara; McDonald, Yolanda J. (Frontiers in Environmental Science, 2022)
Drinking water has and will continue to be at the foundation of our nation’s well-being and there is a growing interest in United States drinking water quality. Nearly 30% of the US population obtained their water from community water systems that did not meet federal regulations in 2019. Given the heavy interactions between society and drinking water quality, this study uses a socio-hydrological approach to evaluate local awareness of drinking water quality issues. By employing text analytics, we explore potential drivers of regional water quality narratives within 25 local news sources across the United States. Specifically, we assess the relationship between printed local newspapers and water quality violations in communities as well as the influence of social, political, and economic factors on the coverage of water quality issues. Results suggest that the occurrence of local drinking water quality violations is not directly reflected in local news coverage, despite the volume and/or frequency of violations. Additionally, news coverage varied across sociodemographic features, with a negative relationship between Hispanic populations and news coverage of Lead and Copper, and a positive relationship among non-Hispanic white populations. These findings extend current understanding of variations in local narratives to consider nuances of water quality issues and indicate opportunities for increasing equity in environmental risk communication.